Analisis Wacana Kritis Komentar Netizen Terhadap Postingan LBGT Pada Laman Influencer TikTok Ockmockey: Analisis Wacana Kritis Norman Fairclough - Apriano I’tisham Adam; Galuh Ahmad Fadhilah; Arya Firman Satriawan (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2024)
The presence of the LGBT (Lesbian, Gay, Bisexual, and Transgender) community has sparked considerable controversy in Indonesia, especially on social media, which has become a popular platform for interaction. TikTok, in particular, has provided a space for the LGBT community to express themselves through sharing content. This study focuses on the opposing attitudes manifesting as discrimination towards the TikTok account @Ockmockey16. The research employs Norman Fairclough's critical discourse analysis technique with a qualitative approach. The findings reveal interactions in the comment section of @Ockmockey16's TikTok account where numerous responses exhibit opposition, employing connotations and metaphors aimed at marginalizing the LGBT community. Examples of such connotations or metaphors include sosis ketemu sosis, pedang pedangan, pisang kepok dan pisang candi, musang jantan dgn musang jantan.